2011
DOI: 10.1111/j.1369-7625.2011.00725.x
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ attitudes towards patient involvement in safety interventions: results of two exploratory studies

Abstract: Background In recent years, patient-focused interventions have been introduced aimed at increasing patient involvement in safetyrelated behaviours. However, patientsÕ attitudes towards these interventions and comfort in participating in the recommended behaviours remain largely unexplored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
0
16

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 53 publications
(100 citation statements)
references
References 28 publications
1
83
0
16
Order By: Relevance
“…78,79 Patients' intentions to participate increased after reading the leaflet. 61 For the booklet, no difference in behaviour was found between the intervention and control group in one study in terms of pointing HCPs towards cleaning their hands. 79 For the other study, patients felt that their behaviour changed upon reading the booklet and that they would be comfortable asking HCPs about HH.…”
Section: Written Strategiesmentioning
confidence: 95%
See 3 more Smart Citations
“…78,79 Patients' intentions to participate increased after reading the leaflet. 61 For the booklet, no difference in behaviour was found between the intervention and control group in one study in terms of pointing HCPs towards cleaning their hands. 79 For the other study, patients felt that their behaviour changed upon reading the booklet and that they would be comfortable asking HCPs about HH.…”
Section: Written Strategiesmentioning
confidence: 95%
“…61 Thirteen articles focused on patients' intentions to participate, 47,60e65,70,71,73,81e83 and three articles examined patients' actual involvement, based on patients' reports 79 (N ¼ 1) or both patients' and HCPs' reports 77,78 …”
Section: Effectiveness Of Single-component Strategiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior research has shown that patients are interested in engaging more in safety efforts [31][32][33] and that physicians, nurses, and other health care professionals support increasing such patient involvement. 31,32 However, interpersonal, intrapersonal, and cultural barriers to patient involvement in safety initiatives exist.…”
Section: Discussionmentioning
confidence: 99%